Evaluación de la biomasa de “Lechuga” (lactuca sativa L.) variedad GREAT LAKES 659, tratados con 4 dosis de gallinaza de aves de postura enriquecida con microorganismos benéficos en la provincia de Lamas - Garcia Mesia, Alessandra Vanessa (2014)
This research work entitled Assessment of the biomass of "Lettuce" (Lactuca sativa L.) GREAT LAKES 659 variety, treaties with four doses of chicken manure from birds of stance enriched with beneficia! microorganisms in Lamas province-San Martín~ it has been developed in Lamas city during two periods, the first harvest of the February 02 to May 03 of 2014, and the second harvest of the May 10 to July 27 2014, whose objectives were apply four doses of chicken manure from birds of position in "lettuce" productíon (Lactuca satíva L.), determíne the performance of the "lettuce" bíomass (Lactuca sativa L.) treaty with the more efficient dose of chicken manure from birds of position and find the effect of chicken droppings of birds of position depending on the "lettuce" biomass (Lactuca sativa L.) influenced by the action of the beneficia) microorganisms applied. In which we have the following question. Is there significant difference in the biomass of lettuce (Lactuca sativa L.) treated with four doses of chicken manure from birds ofposture, in Lamas province- San Martín? The variables were dose of chicken manure from poultry stance. As an indicator: Efficient Microorganisms (independent variable) and lettuce biomass as an indicator: Performance Kg/ ha or kg/m2 and Quality ofleaves: Unit/floor. (Dependent Variable), having the Hypothesis to demonstrate, if we apply 4 doses of poultry droppings of birds of position at the time significant difference exists in the lettuce biomass. Among the treatments evaluated with their respective doses used: T1 (10 TN of chicken manure /Has)= 5.4 kg/treatment, T2 (20 TN of chicken manure /Has) =10.8 kg/treatment, T3 {30 TN of chicken manme /Has)= l6.2 kg/treatment, T4 (40 TN of chicken manure /Has) 21.6 kg/treatment, to witness (Without chicken manure). The conclusions In the frrst crop, the treatments T1 (10 TM.ha-1 ofpoultry droppings), T2 (20 TM.ha-1 ofpoultry droppings), T3 (30 TM.ha-1 ofpoultry droppings) and T4 ( 40 TM.ha-1 of poultry droppings) brought statistically equal averages in performance with 41,875.0 kg ha-1, 53,131.1 kg ha-1, 46,875.0 Kg ha-1, and 41,250.0 Kg ha-1 of performance respectively and overcoming statistically to the average reached by the treatment TO (witness) who brought a lower average with 25,000.0 Kg ha-l. Similar results were in the average weight of the plant and number of leaves for plant. With regard to the plant height, the treatments TI (IO TM.ha-I ofpoultry droppings) and TO (witness) they brought the major averages with 22.78 cm and 22.52 cm ofplant height respectively, overcoming statisticaHy to the averages reached by other treatments. Modal to the diameter of the neck plant, the T2 (20 TM.ha-1 of poultry droppings) it brought the major average with 1,9 cm of diameter, being statistically equal to the treatments TI (10 TM.ha-1 ofpoultry droppings) and T4 (40 TM.ha-I of poultry droppings) who brought averages of 1.7 cm and 1.68 cm of diameter of the neck plant respectively and overcoming statistically to other treatments. In the 2da crop, the treatments T4 (40 TM.ha-I of poultry droppings) and T3 (30 TM.ha-1 of poultry droppings) bmught the· major averages of performance, average plant weight and number of leaves for plant turning out to be statistically equal between yes, with 65,545.6 kg ha-1, 62,523.8 Kg ha-I of performance, 262.2 g and 250.1 g of weight and with 28.9 leaves and 27.7 leaves respectively and overcoming statistically to other treatments. With regard to the height plant the treatment T4 (40 TM.ha-1 of poultry droppings) brought the major average with 29.82 cm, overcoming statistically to other treatments and modal to the diameter of the neck plant, the tre.atm.ent T4 (40 TM.ha-I .ofpo.ultry .droppings) hr:ought the major average with 1.94 cm overcoming statistically to other treatments. In the 2nd crop, the results of the evaluation of the diameter of the neck of the plant, height plant, number leaves for plant, average weight of the plant and performance, emphasized that the increase of the doses of poultry droppings in comparison to the treatment witness adjusted to functions response of the increase of the variables indicated of linear positive character and establishing relations of correlation (r) high between the doses of poultry droppings (independent variable) and variables evaluated (dependent variables). The effects of the application of dose of poultry droppings of position observed with major effi.ciency in the 2da crop. Key words: poultry droppings, "lettuce" production.